Production of Human Endothelial Cells Free from Soluble Xenogeneic Antigens for Bioartificial Small Diameter Vascular Graft Endothelization. (4th June 2015) - Carvalho, Juliana Lott de; Zonari, Alessandra; de Paula, Ana Cláudia Chagas; Martins, Thaís Maria da Mata; Gomes, Dawidson Assis; Goes, Alfredo Miranda
Abstract : Arterial bypass graft implantation remains the primary therapy for patients with advanced cardiovascular disease, but most lack adequate saphenous vein or other conduits for bypass procedures and would benefit from a bioartificial conduit. This study aimed to produce human endothelial cells (hECs) in large scale, free from xenogeneic antigens, to develop a small diameter, compatible vessel for potential use as a vascular graft. Human adipose-derived stromal cells (hASCs) were isolated, cultured, and differentiated in the presence of human serum and used for the reendothelization of a decellularized rat aorta. hASC derived ECs (hASC-ECs) expressed VEGFR2, vWf and CD31 endothelial cell markers, the latter in higher levels than hASCs and HUVECs, and were shown to be functional. Decellularization protocol yielded aortas devoid of cell nuclei, with preserved structure, including a preserved basement membrane. When seeded with hASC-ECs, the decellularized aorta was completely reendothelized, and the hASC-ECs maintained their phenotype in this new condition. hASCs can be differentiated into functional hECs without the use of animal supplements and are capable of reendothelizing a decellularized rat aorta while maintaining their phenotype. The preservation of the basement membrane following decellularization supported the complete reendothelization of the scaffold with no cell migration towards other layers. This approach is potentially useful for rapid obtention of compatible, xenogeneic-free conduit.